2017
DOI: 10.11648/j.ogce.20170506.16
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Steel Corrosion in Simulated Oilfield Acidizing Medium Using Metallic Soap from Local Biomaterial

Abstract: Metallic soap prepared by saponification of melon seed oil (Cucumeropsis mannii N) with copper (II) salt was investigated as corrosion inhibitor for mild steel corrosion in 1 M hydrochloric acid solution. Results reveal that the metallic soap inhibited the corrosion process by spontaneous physical adsorption of the phytochemicals of the seed oil onto the mild steel surface. The highest inhibition efficiency of 82.7% was obtained at 30°C with 10 g/L of the metallic soap, but this efficiency decreased with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The findings of the polarization method indicated that rosemary acts as a cathodic inhibitor. Moreover, the results showed that the inhibition efficiency increases with the increasing concentration; however, the increasing temperature decreases the inhibition property (Ituen et al , 2017; Benabdellah et al , 2006). The plant extracts included natural organic compositions such as alkaloids, tannins containing nitrogen, sulfur, oxygen atoms, different functional groups, double bonds and aromatic rings.…”
Section: Introductionmentioning
confidence: 94%
“…The findings of the polarization method indicated that rosemary acts as a cathodic inhibitor. Moreover, the results showed that the inhibition efficiency increases with the increasing concentration; however, the increasing temperature decreases the inhibition property (Ituen et al , 2017; Benabdellah et al , 2006). The plant extracts included natural organic compositions such as alkaloids, tannins containing nitrogen, sulfur, oxygen atoms, different functional groups, double bonds and aromatic rings.…”
Section: Introductionmentioning
confidence: 94%